DAMPAK SOSIAL-EKONOMI PEMINDAHAN PAKSA: STUDI ATAS PENYINTAS LUMPUR LAPINDO, JAWA TIMUR - Novenanto, Anton (Jurnal Masyarakat dan Budaya, 2019)
This is a study to identify and discuss socio-economic impacts of forced-displacement in the course of Lapindo mudflow in East Java. The main conceptual framework of this study follows previous study which views Lapindo mudflow case as ?disaster of development? for has caused massive forced-displacement of the populations (Novenanto, 2015c). Main themes of discussion of this study will concentrate on migration patterns, loss of access to land and buildings, changing type of work, disruption of access to public facilities and services, and social ties. This study relies on data collected from a community-based research to identify multidimensional impacts of Lapindo mudflow into 6 (six) partner-communities. The data is collected through questionnaire-based survey, focus group discussions, and observations. The research process involved members of each community from research design, collecting data, and data analysis. Such involvement is an implicit strategy to empower them through a continuous practice of critical thinking and logical reasoning which could be additional cultural capital for them in self-empowerment and advocation to the fulfillment and recovery of basic rights in the aftermath of the disaster.